BNBM's exploration of management model - Zhang, Hong; Meng, Fei; Sun, Jing (London : Tsinghua University School of Economics and Management, 2017)
BNBM is a state owned enterprise that manufactures gypsum boards for the construction industry. The enterprise has experience rapid growth since its creation in 2004 and in 2017 launched a business plan to manufacture and sell 3 billion square meters of gypsum boards. This rapid expansion of scale has collided with traditional management models and forced the company to innovate its management model in order to carry out business optimization.
Originally Published InZhang, H., Meng, F., & Sun, J. (2017). BNBM's Exploration of Management Model. 8-817-341. Beijing, China: Tsinghua SEM Chinese Business Case Center.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Bei xin jian cai (ji tuan) you xian gong si (China) -- Case studies; Production management -- China -- Case studies; Drywall -- China